Chief executive officer political connection and firm performance: Evidence from Nigerian listed deposit money banks - Inneh, Eghosa Godwin; Ayoola, Tajudeen John; Obokoh, Lawrence Ogechukwu (Nurture, 2025)
Purpose: Extant studies have investigated the determinants of firm performance; however, limited studies have focused on CEOs' political connections, especially in Nigeria, despite the postulation that the invisible hand of politics controls the economic sector. Our study fills the gap in the literature by examining the effect of the CEO's political connection on the financial performance of the Nigerian Deposit Money Banks. Design/ Approach/Methodology: The scope of this study is limited to the listed Nigerian Deposit Money Banks (DMBs) within the period 2011-2023. We employed a longitudinal research design by collecting 156 firm-year observations resulting from 12 listed DMBs and estimated using the ordinary least square method. Findings: Our study shows that CEO political connection is positive and significantly related to firm performance, supporting the assertion that CEO political connection improves the firm's financial performance, which aligns with the resource dependence theory. Conclusion: the study concluded banks CEO with political connection have a higher performance. Research Limitations/Implications: The study is limited to the Deposit Money Banks (DMBs); hence, we recommend that future studies focus on other sectors of the Nigerian economy. Our study contributed to limited empirical evidence on political connection and firm performance and shows that the CEO's political connection revolves around resource dependence and networking theories.